2001
DOI: 10.1007/s002390010207
|View full text |Cite
|
Sign up to set email alerts
|

Common History at the Origin of the Position-Function Correlation in Transcriptional Regulators in Archaea and Bacteria

Abstract: Abstract. Regulatory proteins in Escherichia coliwith a helix-turn-helix (HTH) DNA binding motif show a position-function correlation such that repressors have this motif predominantly at the N terminus, whereas activators have the motif at the C-terminus extreme. Using this initial collection we identified by sequence comparison the exhaustive set of transcriptional regulators in 17 bacterial and 6 archaeal genomes. This enlarged set shows the same position-function correlation. The main question we address i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…One protein is usually a membrane-linked kinase that, upon sensing the appropriate signal, phosphorylates a DNAbinding protein that mediates transcription from its cognate promoter. Structural analyses have revealed that the helixturn-helix (HTH) signature is the most recurrent DNAbinding motif in prokaryotic transcriptional factors, since almost 95% of all transcriptional factors described in prokaryotes use the HTH motif to bind their target DNA sequences (12,19,27,41,43,104,135,136,302,335,343).…”
Section: Introductionmentioning
confidence: 99%
“…One protein is usually a membrane-linked kinase that, upon sensing the appropriate signal, phosphorylates a DNAbinding protein that mediates transcription from its cognate promoter. Structural analyses have revealed that the helixturn-helix (HTH) signature is the most recurrent DNAbinding motif in prokaryotic transcriptional factors, since almost 95% of all transcriptional factors described in prokaryotes use the HTH motif to bind their target DNA sequences (12,19,27,41,43,104,135,136,302,335,343).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that there is a correlation between the location of the DNA-binding domain and repressor and activator activity. The suggestion was that repressors generally contain an N-terminal DNA-binding domain, while activators generally contain a C-terminal DNA-binding domain (4,5). While this may hold true for many transcription factors, we would advise caution because there are well-documented exceptions to this rule (6).…”
mentioning
confidence: 98%
“…Consistent with the archaeal regulatory systems characterized to date superficially resembling bacterial systems, archaeal and bacterial regulators do appear to have common ancestries (1,16,20). Repressors apparently block, and activators stimulate, transcription initiation by binding to DNA sequences in upstream regions (6,14,21,24).…”
Section: Transcription Initiation Inmentioning
confidence: 57%
“…For the autorepressor Lrs14 (5), Lrs14 and TBP/ TFB binding to the BRE-TATA-box region upstream of lrs14 have been shown to be mutually exclusive, with added Lrs14 incapable of dislodging prebound TFB/TBP in vitro and vice versa. In the one archaeal transcription activation system reproduced in vitro, the activator binds upstream of the BRE/ TATA box, and this increases the affinity of TBP for the TATA-box sequence (19).Consistent with the archaeal regulatory systems characterized to date superficially resembling bacterial systems, archaeal and bacterial regulators do appear to have common ancestries (1,16,20). Repressors apparently block, and activators stimulate, transcription initiation by binding to DNA sequences in upstream regions (6,14,21,24).…”
mentioning
confidence: 96%